Development of Doratoon-Based Animation Audio Visual Media to Improve Cognitive Learning Outcomes in Science Teaching Materials - Mikaelisa Aditya Rehdaya; Dewi Nilam Tyas (Jurnal Penelitian Pendidikan IPA, 2024)
In the learning process, media is quite an important aspect. However, many teachers do not use educational media in teaching, causing low student cognitive learning outcomes. This research aims to: determine the feasibility of Doratoon-based animated audio-visual learning media; to determine the effectiveness of Doratoon-based animated audio-visual learning media in improving student learning outcomes. The ADDIE method (Analysis, Design, Development, Implementation and Evaluation) is a research method used by researchers. Media experts and material experts assess whether media development is suitable for use. The average pretest score for the large group test is 59.70 and the average posttest score is 85. After calculating the N-gain value, we get a value of 0.63, which is included in the medium standard. These figures show that the animated audio visual media developed based on Doratoon can be used and can improve students' cognitive learning outcomes IV